FRI0468 SYSTEMIC AND CUTANEOUS POLYARTERITIS NODOSA IN COLOMBIAN PEDIATRIC PATIENTS: CUTANEOUS POLYARTERITIS IS NOT SO BENIGN. (13th June 2020) - Medina, A.; Calle, M.; Eraso, R.; Hernandez, L.; Peinado Acevedo, J. S.; Velasquez, M.; Vanegas, A.; Jaramillo Arroyave, D.; Muñoz, C.
Abstract : Background: Polyarteritis nodosa (PAN) is the third most frequent vasculitis in pediatrics, Cutaneous PAN (CPAN) being more common that Systemic PAN (SPAN). CPAN is frequently described as a benign disease. In children, PAN onset is frequent between 9 and 11 years of age, with no sex differences, and its clinical features may be nonspecific. Objectives: To characterize pediatric patients who were diagnosed with CPAN and SPAN and to compare their clinical features, treatments, and outcome. Methods: A descriptive study was conducted in two centers from Medellin- Colombia, using retrospective data from January 2010 to December 2019. Patients under 18 years of age classified as PAN according to EULAR/PRINTO/PRES(1) criteria were included. CPAN patients were defined according to EULAR/PRES definition (2). Data from medical records were registered, and were expressed in median and ranges and mean and standard deviation (SD) according to their distribution. A univariate analysis was carried out by comparing signs, symptoms, and treatment between CPAN and SPAN, and a p-value < 0, 05 was considered as significant. Results: Twenty patients were included. The median age at diagnosis was ten years. 60% were boys. The median follow-up period was 27 months. CPAN was diagnosed in 11 (55%) and SPAN in 9 patients (45%). The most frequent symptoms were cutaneous manifestations (95%), fever (60%) and Calf Pain (55%). Mucosal ulcers were described in four patients; 3 of them were defined as CPAN. Lingual necrosis was present in two CPAN, and peripheral nervous system involvement was found in one SPAN and two CPAN patients in skin affected with lesions; even though, no significant statistical differences between CPAN and SPAN were found in constitutional, cutaneous, muscle-skeletal symptoms, and acute phase reactants. Arteriographic anomalies as hepatic and renal microaneurysms, carotidal aneurysms without aortic involvement, and renal infarction were found in one patient each. Skin Biopsy was performed in 18 patients, being compatible with PAN in 16. All PAN patients (CPAN and SPAN) required treatment with glucocorticoids. None of the patients died during the follow-up period. Conclusion: In this Colombian pediatric cohort of PAN patients, the disease was more common in boys than girls, and CPAN was more frequent than SPAN, as already been described. As is evident in this cohort, although CPAN has been considered a benign disease, these patients may be severely ill, requiring glucocorticoid treatment. Pediatric CPAN patients should be strictly followed with particular attention to identify systemic involvement, considering that constitutional, cutaneous, and muscle-skeletal features may be very similar between CPAN and SPAN. References: [1]Ozen S, Pistorio A, Iusan S, et al. EULAR/PRINTO/PRES criteria for Henoch-Schönlein purpura, childhood polyarteritis nodosa, childhood Wegener granulomatosis and childhood Takayasu arteritis: Ankara 2008. Part II: Final classification criteria. Ann Rheum Dis. 2010 May;69(5):798–806. [2]Ozen S, Ruperto N, Dillon M, et al. EULAR/PReS endorsed consensus criteria for the classification of childhood vasculitides. Ann Rheum Dis. 2006;65(7):936–41. Disclosure of Interests: None declared